The partnership of government, society and universities in the process of education quality assurance: the experience of France - N. D. Guskova; E. A. Neretina; YU. R. Enaleeva (Высшее образование в России, 2022)
The paper deals with the specific features of higher education quality assurance in France based on the development of partnership between government, universities and independent agencies. The information about the two independent agencies providing assessment ofeducation quality – AERES and CTI is presented. The results of comparative analysis of Russian and French quality assurance systems in education are discussed with the aim to study the possibility of foreign experience transformation into the practice of Russian universities.